Structural and functional changes in the kidneys of rats with toxic nephropathy after a course of drinking mineral water «DONAT Mg» - Pavliuk, N.; Badiuk, N.; Vasiuk, V. (Journal of Education, Health and Sport, 2022)
Kidney disease of various etiologies affects 6-7% of the total population of the globe. Glomerulonephritis and nephropathy of various etiologies make up a significant part of these kidney lesions. Infectious and non-infectious glomerulonephritis and nephropathy are distinguished, the latter are associated with the influence of environmental factors, including toxic substances, heavy metals and even medications. Magnesium is considered one of the components of the body’s stress-limiting system, since all its effects are aimed at reducing the manifestations of stress and normalizing adaptation processes. A comparative assessment of changes in the kidneys during the simulation of toxic nephropathy and the influence of magnesium-containing agents on the course of the pathology of the experimental model was carried out.